102 Myocardial Fibrosis in Stroke Survivors. (6th June 2015) - Sze, Shirley; Wong, Kenneth
Abstract : Background: Myocardial fibrosis (MF) is a substrate for sudden cardiac death. Cardiac death is the commonest cause of death in stroke survivors. We recently showed that MF in stroke survivors can be treated by spironolactone and amiloride in a randomised placebo-controlled cross-over study. Purpose: To determine the prevalence of severe MF in stroke survivors, as evidenced by Procollagen carboxyl-terminal telopeptide (PICP) >127 µg/L (which is 78% specific and 75% sensitive at diagnosing severe fibrosis, as identified by histological assessment of myocardial biopsy). We also tested the hypothesis that PICP is associated with reversible cardiac pathologies in stroke survivors. Methods: 186 stroke survivors were studied. Patients who were known to have liver or lung fibrosis or recent surgery (within last 6 months), or atrial fibrillation were excluded at recruitment because these conditions can affect PICP levels. The concentration of PICP was measured by radioimmunoassay using a kit from Orion Diagnostics, Finland (assay coefficient of variation; = 1.48%). Dipyridamole myocardial perfusion imaging was performed. Ejection fraction was determined using gated SPECT. Left ventricular mass index (LVMI) was determined by echocardiography. Results: 186 stroke survivors (111 male, 75 female) were studied. Severe MF is prevalent amongst stroke survivors. 36% (67 out of 186) had PICP >127 µg/L. Stroke survivors with severe fibrosis were older [68 (8) vs 65 (10), p = 0.049], but had similar blood pressure (144/79 mmHg in severe fibrosis patients, vs 144/80 mmHg), history of angina or myocardial infarction and degree of inducible ischaemia (0, interquartile range (IQR) = 0–3, vs 0 (IQR 0–4), p = 0.79) when compared with those with lower PICP levels (Table 1 ). There was a very weak correlation between PICP and LVMI [r = 0.2, p = 0.011]. No correlation was found between PICP and ejection fraction or BNP levels at rest or QT dispersion (Table 2 ). Interestingly, stroke survivors taking ACE-inhibitors had less severe MF (Mantel-Haenszel OR = 0.3, 95% CI = 0.15–0.74; Fisher's exact 2-sided p = 0.007). Conclusions: Severe MF is common in stroke survivors. Whilst a statistically significant association was found between MF and LVMI, the correlation is very weak.